BISAKAH LEMBAGA HUKUM ADAT MEMINIMALISIR PERNIKAHAN SIRRI? - Mujib, M. Misbahul (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2014)
Sirri marriage actually has negative implications on the society. Logically a causation of Sirri marriage is caused by customary law. Unwritten character of customary law which causes all decisions or products, including marriage is not well written. This paper aims to know how the customary law minimize sirri marriage, can the customary law do it. It is realistic of course if then customary law institutions minimize Sirri marriage because one of reasons for the growth of Sirri marriage is customary law. Making customary law institutions as part of the national legal institutions can be used as an alternative to minimize Sirri marriage. The relationship between customary law with national law should be developed in the direction of strengthening the institutions of customary law as part of the national legal institutions. The defining of sirri marriage should be extended to have proof of marriage. Powers noted wedding events should also be extended to customary law institutions not only KUA or civil records only, or at least braided communication between KUA, the civil institutions and customary lawinstitution.[Pernikahan sirri secara nyata mempunyai implikasi negatif di dalam masyarakat. Secara logis perkembangan nikah sirri salah satunya disebabkan oleh hukum adat. Karakter hukum adat yang tidak tertulis menyebabkan semua putusan ataupun produk hukum adat termasuk pernikahan juga tidak tertulis. Tulisan ini bertujuan bagaimana menjadikan hukum adat dapat meminimalisirpernikahan sirri. Adalah realistis tentunya kalau kemudian upaya meminimalisir pernikahan sirri bisa melalui lembaga hukum adat, karena salah satu sebab tumbuhnya pernikahan sirri adalah hukum adat. Menjadikan lembaga hukum adat sebagai bagian dari lembaga hukum nasional bisa dijadikan alternatif untuk meminimalisir pernikahan sirri. Hubungan antara hukum adat dengan hukum nasional harus dikembangkan ke arah penguatan lembaga hukum adat sebagai bagian dari lembaga hukum nasional. Pemaknaaan nikah sirri harus diperluas menjadi nikah yang mempunyai bukti. Wewenang mencatat peristiwa pernikahan harus juga diperluas kepada lembaga hukum adat bukan hanya KUAatau catatan sipil semata, atau setidaknya dijalin komunikasi antara KUA, catatan sipil dengan lembaga hukum adat].